Using riverscape genetics to investigate the genetic response of two species and their life-history forms to dam removal - Ledger, Kimberly J.; Su, Yingxin; Jeon, Jong Yoon; Fullerton, Aimee H.; Kuligowski, David; Bennett, Todd; Denton, Keith; McHenry, Michael; McMillan, John H.; Anderson, Joseph H.; Connor, Heidi; Seamons, Todd R.; et al. (Frontiers in Ecology and Evolution, 2023)
Barriers such as hydroelectric dams inhibit migratory pathways essential to many aquatic species, resulting in significant losses of species, their unique life-history forms, and genetic diversity. Understanding the impacts of dam removal to species recovery at these different biological levels is crucial to fully understand the restoration response. We used the removal of two large dams on the Elwha River as an opportunity to characterize how restored connectivity impacts the reestablishment of two fish species Chinook salmon (Oncorhynchus tshawytscha), and Steelhead/rainbow trout (Oncorhynchus mykiss) and their unique ocean migration return-timing life-history forms. In this study, we employed riverscape genetics to understand how restoration and the environment influence the distribution of neutral and return-timing genetic variation underlying the migratory life-history forms and species at-and between-sampling sites. We genotyped fish sampled over time and space in the Elwha River using GTsequencing loci for both species at neutral and putatively adaptive loci in and near the major effect genic region GREB1L/ROCK1 putatively associated with migration timing. We observed little evidence of genetic structure for either species, but a statistically significant increase in early return-timing alleles in upriver O. mykiss population post-dam removal. For O. tshawytscha, at-site genetic variation was shaped by river distance and a combination of environmental habitat differences, while between-site genetic variation was mainly shaped by river distance. For all O. mykiss, at-and between-site genetic variation is primarily explained by river distance. Genetic variation in juvenile and adult Steelhead, respectively, were influenced by at-and between-site environmental and habitat differences. Our study illustrates the power of using genetics to understand the implications of both demography and environment in facilitating the recovery of species and their diverse life-history forms following barrier removal.